Die Fischerei im Nordostatlantik im Jahre 2004 - Schöne, Rüdiger; Ulleweit, Jens (2005)
Since 1990 North-east Atlantic fish species – arctic cod, saithe, haddock, redfish and Greenland halibut – have been investigated by on-board observers on the German commercial trawler FMS Kiel. These investigations are part of the national data collection regulation established by the European Union in recent years. Collected data are basic data for the scientific assessment of these important fish stocks of the European fisheries. The results of the observed cruises are used by the Arctic Fisheries Working Group of the International Council for the Exploration of the Seas (ICES). Biological investigations were carried out in Norwegian waters and the Barents Sea (ICES Divisions IIa and IIb) on board FMS Kiel in January to March and in August/September 2004. This report presents results of these cruises and an overview about the general fishery situation in 2004.